Improving complementary feeding through community-based management of malnutrition in Rural India - Murugan, Ganapathy; Gope, Rajkumar; Dhingra, Nidhi (International Food Policy Research Institute, 2015)
A baseline survey conducted during 2012 among selected districts with extremely marginalized populations in Bihar, Chhattisgarh, Jharkhand, and Odisha revealed high rates of malnutrition and poor infant and young child feeding (IYCF) practices. Among 3,489 children surveyed, 60.2 percent were stunted, 55.1 percent were underweight, and 24.4 percent were wasted. Only 23.9 percent of the children age 6–36 months received appropriate feeding from diverse food groups (AAM Unpublished).